The Value of an Incomplete Degree: Heterogeneity in the Labor Market Benefits of College Non-Completion. (6th June 2020) - Giani, Matt S.; Attewell, Paul; Walling, David
ABSTRACT: Many undergraduates leave college without completing a degree or credential. Some researchers characterize this as a waste of the student's time because (they assert) college short of a degree does not yield any advantage in the labor market. Using data for an entire cohort of students graduating high school in Texas in one year, we compare the employment and earnings years later of those who do not go beyond high school with those who enter college but do not complete a credential. Using techniques that address selection bias, we find that students with "some college" are considerably more likely to be employed fifteen years after high school graduation and tend to earn significantly more than their counterparts who do not go to college. These benefits are found across student subgroups, with low-income students, women, and students of color generally experiencing the greatest improvements in labor outcomes from college attendance. While college dropouts do not fare as well as college graduates, incomplete college nevertheless functions for many as a stepping-stone into a better labor market position.